Address at the opening of the thirtieth session - Pim, Jonathan (Statistical and Social Inquiry Society of Ireland, 1876)
The honour you have done me in electing me as your president, brings with it the responsibility of addressing you on the occasion of this, the opening meeting of the thirtieth session of the Statistical Society. Having been a member of the Society ever since its foundation, my thoughts have been directed to the consideration of the work which it has done in the twenty-nine years of its existence, and of the changes in the social and economic condition of Ireland which have taken place during that period.
Read before the Society, 28 November 1876
Keywords: Statistical and Social Inquiry Society of Ireland; Irish agriculture; Economic history; 314.15